Fat-free mass index in a diverse sample of male collegiate athletes - Currier, B. S.; Harty, P. S.; Zabriskie, H. A.; Stecker, R. A.; Moon, J. M.; Jagim, A. R.; Kerksick, C. M. (The Journal of Strength and Conditioning Research, 2019)
Fat-free mass index (FFMI) is a body composition metric that has been used to assess relative muscularity in athletes. Fat-free mass index is calculated by dividing FFM by height squared, although further height corrections through linear regression may be needed in taller individuals. This study reported height-adjusted FFMI (FFMIAdj) data in 209 male collegiate athletes from 10 sports (baseball, cross country, football, golf, ice hockey, weightlifting, rugby, swimming, track and field, and water polo) and the FFMIAdj natural upper limit for sports with sufficient sample size. The body composition of all subjects (mean ± SD; age: 20.7 ± 1.9 years, height: 182.9 ± 6.7 cm, body mass: 90.8 ± 16.8 kg, and percent body fat: 15.6 ± 5.3) was measured using dual-energy x-ray absorptiometry. Linear regression was used to adjust for height, and the FFMIAdj natural upper limit was determined by calculating the 97.5th percentile of all values. One-way analyses of variance with Games-Howell post hoc comparisons were used to determine between-sport differences. A paired-samples t-test revealed a significant difference (p < 0.001) between unadjusted and adjusted mean FFMI values. The overall mean FFMIAdj was 22.8 ± 2.8 kg·m-2. Significant between-sport differences (p < 0.001) in FFMIAdj were identified. Average FFMIAdj was highest in football athletes (24.28 ± 2.39 kg·m-2) and lowest in water polo athletes (20.68 ± 3.56 kg·m-2). The FFMIAdj upper limit was calculated for all athletes (28.32 kg·m-2), rugby (29.1 kg·m-2), and baseball (25.5 kg·m-2). This study reported FFMIAdj values in a diverse cohort of male collegiate athletes, providing data for the first time in several sports. These values can be used to guide nutritional and exercise interventions, predict athletic performance, and provide coaches with standardized information regarding the potential for further FFM accretion in male athletes.